Backpack magnetic sprayer: off-target drift and on-target deposition uniformity in a sugarcane plantation - Moges, Girma; Mcdonnell, Kevin; Delele, Mulugeta A. (International Journal of Agricultural and Biological Engineering, 2021)
There is an increasing requirement for new application methods that are capable of minimizing agricultural spray drift and maximizing on-target deposition. Magnetic charge spraying techniques improve the adhesion characteristics of the spray solution to agricultural crops which in turn can reduce the amount of solution to be sprayed in comparison with the conventional spraying method that uses non-charged spray droplets. In this research, experimental field studies were conducted to evaluate the effects of magnetic spraying technology taking into account the effect of meteorological parameters on spray drift and on-target deposition in a sugarcane plantation. The results showed a significant benefit from magnetic spraying on drift reduction, in comparison with conventional knapsack and backpack boom sprayers. The lowest drift values were achieved with magnetic sprayer with TeeJetXR110015 nozzle; it was significantly lower than conventional backpack boom sprayer with both TeeJetXR110015 and TeeJetXR11001 nozzles and knapsack sprayer. Significant differences between treatments were also observed for on-target spray deposits at both top and middle canopies. The highest deposition was obtained by magnetic sprayer with TeeJetXR110015 nozzle at both upper and middle canopies. However, the deposition for the magnetic sprayer coupled with TeeJetXR11001 nozzle was statistically at par with knapsack at upper canopy and with both knapsack and backpack boom sprayers with TeeJetXR110015 nozzle in middle canopy. None of the application methods except magnetic sprayer with TeeJetXR110015 gave acceptable spray deposition uniformity. In conclusion, the result clearly showed that the potential of magnetic spraying technology in reducing pesticide drift and improving on-target deposition in crop spraying.Keywords: magnetic sprayer, nozzle, drift, deposition, drift curve, sugarcaneDOI: 10.25165/j.ijabe.20211406.6282Citation: Moges G, McDonnell K, Delele M A. Backpack magnetic sprayer: off-target drift and on-target deposition uniformity in a sugarcane plantation. Int J Agric & Biol Eng, 2021; 14(6): 27–36.